Sociodemographic Characteristics of Persons Treated in the High Security Forensic Psychiatry Service: A Retrospective Study - Emir, Burcu Sırlıer; Kılıçaslan, Aslı Kazğan; Kurt, Osman; Yildiz, Sevler (My University, 2022)
Aim: In the study, it is aimed to analyze the sociodemographic characteristics of the convicted patients, who were treated in the High-Security Forensic Psychiatry Services (HSFPS) of Elazig Fethi Sekin City Hospital within a period of one year. Material and Methods: 409 convicted psychiatric patients, who applied to Elazig Fethi Sekin City Hospital High-Security Forensic Psychiatry Service were included in this study between March 2020 and March 2021. Personal data pertaining to these patients were obtained from hospital archive records. A general information questionnaire including sociodemographic data prepared by the authors, was used in the study. The sociodemography data form consists of 20 questions in total.Results: The analysis of the collected data revealed that the convicted psychiatric patients were mostly single or divorced, that they lived mostly in the city, that 51.1% of them have not worked at any job, that 40.7% of them had a psychiatric disorder with psychotic features, that 84.4% of them committed a crime for the first time and that these crimes were mostly directed at other individuals.Conclusion: In our study, it was observed that the diagnosis of schizophrenia or other psychotic disorders was more common in the convicted group. The high unemployment rate shows the importance of vocational rehabilitation, and the high number of untreated patients shows that closer follow-up will be beneficial. This study shows that applications to high-security forensic psychiatry services are high and it may be beneficial to increase their number throughout the country.
Keywords: High-security forensic psychiatry service; prophlylactic treatment; medical observation; sociodemographic characteris